PWE-132 The Prevalence and Clinical Significance of Cryoglobulinaemia in a Scottish Cohort of Hepatitis C Patients. (4th June 2013) - Swann, R E; Robinson, M; Barclay, S; Priest, M; Mills, P; McLauchlan, J; Patel, A
Abstract : Introduction: Hepatitis C virus (HCV) infection is the most common cause of cryoglobulinaemia – a clonal B cell disorder characterised by precipitation of antibody aggregates on serum cooling. This can lead to vasculitic symptoms and complications including renal failure [1]. One meta-analysis suggested a prevalence of 44% in HCV infected patients. However, other studies have reported much lower rates [2]. Genotype is thought to influence prevalence, and data from the UK, where 45% of cases are genotype 3, is unknown. This study aimed to determine the prevalence of cryoglobulinaemia in a cohort of HCV infected patients and identify any associated clinical features. Methods: 75 patients with chronic G1 or G3 HCV were prospectively recruited from liver clinics in addition to 20 healthy controls. None had a prior diagnosis of cryoglobulinaemia. Each patient completed a symptom questionnaire and clinical and laboratory details were recorded. A whole blood sample was collected and maintained at 37°C until serum had been separated using a heated centrifuge. Serum was stored at 4°C for 7 days. A patient was recorded as cryoglobulin positive if a precipitate formed which disappeared on re-warming. Clinical features were correlated with presence of cryoglobulin. Results: Adequate samples were received in 65/75 HCV infected patients (31 G1, 34 G3). Of these, 35.4% (23/65) had detectable cryoglobulin. No cryoglobulin was detected in the healthy control samples. Clinical associations are listed below (p values from Fisher's Exact Test unless otherwise stated). There was no difference in prevalence of IVDU or Diabetes in those with cryoglobulins. No individual symptom was associated with cryoglobulin detection. Conclusion: Cryoglobulinaemia has a surprisingly high prevalence of 35% within our UK based cohort of HCV patients, being less common in males. Symptoms are non-specific and occur in the absence of detectable cryoglobulin with no association between symptoms and cryoglobulin positivity. There was a non-significant trend to association with cirrhosis and genotype 3 as shown in previous studies. Cryoglobulinaemia may have been underdiagnosed previously due to practical difficulties with testing and it should be considered in any patients with renal dysfunction and HCV. References: Adv Hematol 2011 doi:10.1155/2011/835314 Hepatology 2002; 36:978–985